LGR5-Positive Supporting Cells Survive Ototoxic Trauma in the Adult Mouse Cochlea - Smith-Cortinez, Natalia; Yadak, Rana; Hendriksen, Ferry G. J.; Sanders, Eefje; Ramekers, Dyan; Stokroos, Robert J.; Versnel, Huib; Straatman, Louise V. (Frontiers in Molecular Neuroscience, 2021)
Sensorineural hearing loss is mainly caused by irreversible damage to sensory hair cells (HCs). A subgroup of supporting cells (SCs) in the cochlea express leucine-rich repeat-containing G-protein coupled receptor 5 (LGR5), a marker for tissue-resident stem cells. LGR5+ SCs could be used as an endogenous source of stem cells for regeneration of HCs to treat hearing loss. Here, we report long-term presence of LGR5+ SCs in the mature adult cochlea and survival of LGR5+ SCs after severe ototoxic trauma characterized by partial loss of inner HCs and complete loss of outer HCs. Surviving LGR5+ SCs (confirmed by positive LGR5-GFP expression) were located in the third row of Deiters’ cells. We observed a change in the intracellular localization of LGR5, from the nucleus in normal-hearing to cytoplasm and membrane in deafened mice. These data suggests that the adult mammalian cochlea possesses properties essential for regeneration even after severe ototoxic trauma.